Levels of competence of elementary science teachers in the Gerona South District of Tarlac - Dugay, Remedios Pasamonte 1946- (1975)
A total of 108 science teachers in 16 complete elementary and 7 primary schools were tested for subject matter competency and competency in teaching skills using the Test for Elementary Science Teachers (TFEST) and the Teaching Observational Instrument (TOI). TFEST results showed average score of 15.55 (71 percent) in the Process Test and 19.10 (48 percent) in the Content Test, indicating that the teachers are more competent on the science processes than on the concepts. The total mean score was 33.62 (54 percent), or moderately satisfactory knowledge in the content of the elementary science program. The teachers were found to strongly employ reinforcement, pre-instruction procedure (set), lecture and use of audio-visual aids, illustrating and use of examples, variation of stimulus situation, closure, and pupil-initiated questions.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Science teachers -- Gerona, Tarlac